The Added Value of Trabecular Bone Score in Fracture Risk Assessment of Kidney Transplant Recipients (Iranian Journal of Kidney Diseases, 2020)
Introduction. Trabecular Bone Score (TBS) is an index of bone microarchitecture independent of Bone Mineral Density (BMD). Recently, TBS data has been used to optimize the predictive value of the Fracture Risk Assessment Tool (FRAX). The aim of this study was to evaluate the clinical value of FRAX adjustment with TBS in kidney transplant recipients. Methods. Seventy post-transplant Iranian kidney recipients were included in this study. After the evaluation of BMD and TBS, the risk of major osteoporotic fracture (MOF) and hip fracture (HF) was assessed once with and once without TBS adjustment. The proportion of patients who needed a therapeutic intervention was compared before and after TBS adjustment. The association between TBS and BMD data was also evaluated. Results. The mean age of the patients was 54 ± 8.8 years (range: 40 to 77). The mean TBS of the patients was 1.30 ± 0.12. In multivariate analysis, the TBS was significantly associated with the age (P < .05) and dialysis period (P < .05). A strong correlation was found between the spine BMD and TBS data (r = 0.612, P < .001). A significant correlation was found between the MOF and HF of the patients before and after adjustment for TBS. The proportion of patients needed a therapeutic intervention significantly increased from 17.1% to 25.7% after TBS adjustment of FRAX. Conclusion. Adjustment of FRAX with TBS will reclassify the treatment decision in a considerable number of kidney transplant recipients. This clinical value warrants the adjustment of FRAX data with TBS in future workouts.